Krox20 hindbrain regulation incorporates multiple modes of cooperation between cis-acting elements - Thierion, Elodie; Le Men, Johan; Collombet, Samuel; Hernandez, Céline; Coulpier, Fanny; Torbey, Patrick; Thomas-Chollier, Morgane; Noordermeer, Daan; Charnay, Patrick; Gilardi-Hebenstreit, Pascale (PLoS genetics, 2017)
Developmental genes can harbour multiple transcriptional enhancers that act simultaneously or in succession to achieve robust and precise spatiotemporal expression. However, the mechanisms underlying cooperation between cis-acting elements are poorly documented, notably in vertebrates. The mouse gene Krox20 encodes a transcription factor required for the specification of two segments (rhombomeres) of the developing hindbrain. In rhombomere 3, Krox20 is subject to direct positive feedback governed by an autoregulatory enhancer, element A. In contrast, a second enhancer, element C, distant by 70 kb, is active from the initiation of transcription independent of the presence of the KROX20 protein. Here, using both enhancer knock-outs and investigations of chromatin organisation, we show that element C possesses a dual activity: besides its classical enhancer function, it is also permanently required in cis to potentiate the autoregulatory activity of element A, by increasing its chromatin accessibility. This work uncovers a novel, asymmetrical, long-range mode of cooperation between cis-acting elements that might be essential to avoid promiscuous activation of positive autoregulatory elements.